Immediate and long-term results of aortic valve replacement with University of Cape Town aortic valve prosthesis - Schrire, V. (1970)
Aortic valve replacement with the University of Cape Town lenticular prosthesis was performed in 149 patients during a six-year period, almost all patients being severely disabled with advanced heart disease. There was a hospital mortality of 12 per cent. Bacterial endocarditis was a serious complication and accounted for three hospital and five long-term deaths. The survivors were followed for periods of up to 72 months (average 24), the minimum period of observation being six months. There were 23 late deaths due to heart disease, of which 5 where due to myocardial failure. Myocardial failure unrelieved or only temporarily alleviated by the operation occurred in three surviving patients. The main problems have been sudden death and systemic embolism. Some of the cases of sudden death were due to coronary artery embolism, but in a number the cause could not be determined even at necropsy, and they were presumed to be due to arrhythmia. Both complications appeared to be related to valve design. A bare steel seat was associated with a high incidence of both complications, whereas a woven Dacron-velour cloth-covered seat almost eliminated embolism and reduced the incidence of sudden death. Long-term anticoagulant therapy appears to be of no real value with the cloth-covered valve. Gratifying results were obtained in the surviving patients with loss of all symptoms in 80 per cent and improvement in almost all patients. This improvement or relief of symptoms was maintained in most patients throughout the period of study.